2022
DOI: 10.1186/s12889-022-12810-z
|View full text |Cite
|
Sign up to set email alerts
|

The association of the age, period, and birth cohort with 15-year changes in body mass index and waist circumference in adults: Tehran lipid and glucose study (TLGS)

Abstract: Objective To examine the association of age, period, and birth cohort with body mass index (BMI) and waist circumference (WC) changes among the participants of the Tehran Lipid and Glucose Study from 1999 to 2015. Methods This prospective cohort study included 4895 participants aged ≥20 years (41.3% men), who were divided into twelve gender stratified groups, having a ten-year age difference between them. Analyses were conducted to explicitly asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Periodontal disease, overweight/obesity and NCDs such as diabetes are closely related due to common risk factors, comprising especially excess sugar ingesting and communal inflammatory pathways [ 35 ]. In the present study BMI tended to increase with age contributing to the increase in waist circumference [ 36 ] which are known to be associated to periodontal disease [ 37 , 38 ]. In the age group of 18–39 years, the only significant predictor for periodontal status was ‘waist circumference’.…”
Section: Discussionmentioning
confidence: 90%
“…Periodontal disease, overweight/obesity and NCDs such as diabetes are closely related due to common risk factors, comprising especially excess sugar ingesting and communal inflammatory pathways [ 35 ]. In the present study BMI tended to increase with age contributing to the increase in waist circumference [ 36 ] which are known to be associated to periodontal disease [ 37 , 38 ]. In the age group of 18–39 years, the only significant predictor for periodontal status was ‘waist circumference’.…”
Section: Discussionmentioning
confidence: 90%
“…Plenty of evidence suggested that WC increased throughout most of adult life. A recent 15-year longitudinal study evaluated sex-speci c changes in WC in the adult population and found that an increase in WC was strongly associated with aging [45].…”
Section: Multilevel Logistic Regression Analysismentioning
confidence: 99%